Pola Konstruksi Klitik Bahasa Tolaki - Hilaluddin Hanafi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
Tolakinese is one of the dominant languages used in South East Sulawesi. Like other languages, Tolakinese also recognizes the forms of clitic. This paper discusses the construction pattern of clitic in Tolakinese language and classifies it into two forms: proclitic and enclitic. These two forms are classified based on their distribution criteria. Proclitic is a clitic preceding its host, while enclitic is a clitic that follows its host.